2004
DOI: 10.3189/172756404781815257
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of micropenetration resistance in snow layers on a small slope

Abstract: The mechanisms leading to dry-snow slab release are influenced by the three-dimensional variability of the snow cover. We measured 113 profiles of penetration resistance with a snow micropenetrometer on an alpine snow slope. Seven distinct layers were visually identified in all snow micropenetrometer profiles. The penetration resistance of adjacent layers did not change abruptly, but gradually across layer boundaries that were typically 2 mm thick. In two layers, penetration resistance varied around 200% over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…Previous studies of many point measurements at the slope scale using the SMP revealed, among other things, that typical weak layers are often continuously present but have clearly varying properties (e.g., Kronholm et al, 2004). However, relating spatial variations as derived from point measurements to slope stability has so far not been successful.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of many point measurements at the slope scale using the SMP revealed, among other things, that typical weak layers are often continuously present but have clearly varying properties (e.g., Kronholm et al, 2004). However, relating spatial variations as derived from point measurements to slope stability has so far not been successful.…”
Section: Introductionmentioning
confidence: 99%
“…A time-consuming but essential part of spatial variability analysis is the manual matching of the stratigraphic sequence (e.g., Kronholm et al, 2004). For this reason, previous studies have focused on a relatively few number of layers (e.g., 11 layers by Kronholm et al, 2004, 5-10 layers by Sturm and Benson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The true spatial variability on a decameter scale is mainly due to the wind in cold winter months . This factor leads to a continuous depth-variation of the snow layers but preserves the main features of the profiles, when these are measured within tens of meters distance in smooth terrain (Harper and Bradford, 2003;Kronholm et al, 2004;Tape et al, 2010). Spatial variation of snow layer depth may affect snow internal processes such as pressure sintering, and may therefore yield spatial variability in intensive properties such as density or hardness (Schweizer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The layering affects the thermal conductivity and may direct and block the flow of water vapor and melt water (Colbeck, 1991). Layers formed during windy conditions are likely to be more spatially variable than other layers (Kronholm et al, 2004).…”
Section: Introductionmentioning
confidence: 99%